Understanding health seeking behavior - Oberoi, Simmi (J Family Med Prim Care, 2016)
Leaving conventional “Dai” assisted home delivery to opt for institutional delivery is not unusual followed by shift from rural to urban living. However, this case, in particular, is oddly different. Hence, a deeper insight is warranted leading to a view that is unique. While analyzing the reasons it stands as a pointer in policy formulation, a necessity to understand such cases. Health belief model is applied in arriving at the inferences. It is often not just what is offered that makes bait but how it is perceived by the recipient matters. This can be visualized by this case study.